STATE EXCISE TAXES BACKGROUND AND STRATEGY OVERVIEW FOR SAMPLE STATES 840711 (Tufts Archival Research Center, 2007)
Outline of strategy for addressing the issue of excise taxes. Use three states (Minnesota, Texas and California) as case studies to provide examples. Provides a history of the tax issue as well as the arguments that have worked best in each state. Lists various groups that are sympathetic to or allies of the tobacco industry and key people that have helped their efforts.